Statyczna Wytrzymałość Wielkich Elementów Stalowych przy Niższych Temperaturach Materiału - J. Nèmec (Engineering Transactions, 1965)
The paper discusses the influence of the temperature and the size of steel machine elements on their destruction type and the ultimate load. At lower temperatures greater liability to brittle cracking is observed for notched elements. At normal temperature a tendency to brittle cracking is observed for large notched elements of 100 cm2 sectional area, even if they are made of low carbon steel. The causes of brittle cracking of large elements are discussed on the basis of tests performed in Czechoslovakia using a strength testing machine of 8.000 tons maximum load. These tensile tests have been performed for elements of cross sectional area up to 1200 cm2.